Modeling and real-time control of urban drainage systems: A review. (November 2015) - García, L.; Barreiro-Gomez, J.; Escobar, E.; Téllez, D.; Quijano, N.; Ocampo-Martinez, C.
Highlights: Literature review of the main modeling approaches toward the real-time control for urban drainage systems proposing a criterion for their classification. Description and comparison of the main real-time control strategies applied to urban drainage systems, and analysis based on a reported case study. Outline of the most common software tools used for both modeling and control of urban drainage systems, and their suitability for each case. Discussion and statement of the main references related to safe mechanisms for ensuring the proper urban drainage systems operation. Abstract: Urban drainage systems (UDS) may be considered large-scale systems given their large number of associated states and decision actions, making challenging their real-time control (RTC) design. Moreover, the complexity of the dynamics of the UDS makes necessary the development of strategies for the control design. This paper reviews and discusses several techniques and strategies commonly used for the control of UDS. Moreover, the models to describe, simulate, and control the transport of wastewater in UDS are also reviewed.